The Influence of Content Quality on Social Media on Customer Loyalty Dapur Cokelat Products In Indonesia - Lestari, Unik Dwi; Hasan, Manal Mohamed; Nadif, Muhammad Akhdan; Rojuaniah, Rojuaniah; Ikramina, Ikramina (HK-Publishing, 2023)
Abstract:This study aims to analyze the effect of content quality on customer loyalty and word of mouth through stickiness in Dapur Cokelat Indonesia customers. With this, it is hoped that it can provide input to the Management of Dapur Cokelat Indonesia in increasing customer loyalty through the quality of content on social media. This research will be conducted in Indonesia in July 2023. The data collection process is carried out by distributing questionnaires online through Google Forms. Furthermore, this study used purposive sampling to determine respondents. This research was conducted on 175 customers who had purchased Dapur Cokelat products online. The resulting data is analyzed using the Structural Equation Model (SEM) method. The results of this study show the positive influence of content quality on relationship quality, attitudinal loyalty, behavioral loyalty, and word of mouth. However, this study also shows that content quality does not have a positive effect on stickiness.Keywords:Â content quality, relationship quality, stickiness, attitudinal loyalty, behavioral loyaltyAbstract:Penelitian ini bertujuan untuk menganalisis tentang pengaruh content quality terhadap loyalitas pelanggan dan word of mouth melalui stickiness pada pelanggan Dapur Cokelat Indonesia. Dengan ini harapannya dapat memberikan masukan kepada Manajemen Dapur Cokelat Indonesia dalam meningkatkan loyalitas pelanggannya melalui kualitas konten pada media sosial. Penelitian ini dilakukan di Indonesia pada bulan Juli 2023. Proses pengumpulan data dilakukan dengan menyebar kuesioner secara online melalui Google Form. Selanjutnya penelitian ini menggunakan purposive sampling untuk menentukan responden. Penelitian ini dilakukan pada 175 pelanggan yang pernah membeli produk Dapur Cokelat melalui online. Data yang dihasilkan dianalisa dengan menggunakan metode Structural Equation Model (SEM). Hasil dari penelitian ini menunjukkan pengaruh positif dari content quality terhadap relationship quality, attitudinal loyalty, behavioral loyalty, dan word of mouth. Namun, pada penelitian ini juga menunjukkan bahwa content quality tidak berpengaruh positif terhadap stickiness.Kata Kunci: kualitas konten, kualitas hubungan, kelekatan, loyalitas sikap, loyalitas perilaku